Pituitary adenomas and cerebrovascular disease: A review on pathophysiology, prevalence, and treatment - Osorio, Robert C.; Oh, Jun Y.; Choudhary, Nikita; Lad, Meeki; Savastano, Luis; Aghi, Manish K. (Frontiers in Endocrinology, 2022)
Pituitary adenomas (PAs) have been shown to cause excess cardiovascular disease comorbidity and mortality. Cerebrovascular disease (CeVD) is a small subset of cardiovascular disease with high morbidity, and its risk in patients with pituitary adenomas has been sparingly explored. In this review, we examine what is known about the prevalence of cerebrovascular disease in patients with PAs, from its initial discovery in 1970 to present. An abundance of literature describes increased cerebrovascular mortality in patients with acromegaly, while research on other PA subtypes is less frequent but shows a similarly elevated CeVD mortality relative to healthy populations. We also review how cerebrovascular risk changes after PAs are treated, with PA treatment appearing to prevent further accumulation of cerebrovascular risk without reversing prior elevations. While acromegaly-associated CeVD appears to be caused by elevated growth hormone (GH) levels and Cushing disease’s elevated glucocorticoids similarly cause durable alterations in cerebrovascular structure and function, less is known about the mechanisms behind CeVD in other PA subpopulations. Proposed pathophysiologies include growth hormone deficiency inducing vessel wall damage or other hormone deficits causing increased atherosclerotic disease. Early diagnosis and treatment of PAs may be the key to minimizing lifetime CeVD risk elevations. More research is needed to better understand the mechanisms behind the increased CeVD seen in patients with PAs. Physicians caring for PA patients must remain vigilant for signs and symptoms of cerebrovascular disease in this patient population.